Better the Devil You Know? How Fringe Terrorism Can Induce an Advantage for Moderate Nonviolent Campaigns - Belgioioso, Margherita (Terrorism and political violence, 2021)
Fringe terrorism is common during nonviolent campaigns. We examine how this can modify the strategic environment between dissident groups and the state in ways that present both challenges and opportunities to moderate factions. Terrorism is intended to promote violent escalation in a conflict, but we argue that fringe terrorist activities in a nonviolent campaign under certain conditions can induce an advantage for well-organized moderate factions. The risk of escalation following terrorism can give the government more incentives to offer concessions to moderate campaign leaders if the movement can credibly prevent armed escalation. The ability to control and prevent violence is more likely when nonviolent movements have a hierarchical structure and a centralized leadership, as such campaigns are better able to prevent shifts by supporters towards violent fringes. Using new data on terrorist attacks by factions sharing the same overall objectives as ongoing nonviolent campaigns, we show that nonviolent campaigns are more likely to see substantial gains in spite of fringe terrorist activities when a movement has a hierarchical structure and a centralized leadership.